Peran Humas Digital (Cyber PR) dalam Membangun Branding Sekolah Berbasis Teknologi - Nazwa Bunga Alzira Rimosa; Sulis Maryati (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study aims to understand the concept of digital public relations (Cyber Public Relations/Cyber PR) in the field of education and to describe its role in building technology-based school branding. The study employs a qualitative approach using library research. Data were collected from various scientific sources, including national journal articles, books, conference proceedings, and other relevant scholarly documents, and were analyzed using content analysis techniques through the processes of identification, categorization, interpretation, and synthesis. The results of the study indicate that digital public relations represent a transformation of public relations practices that utilizes digital technology as a strategic communication medium to build relationships with the public in an interactive, transparent, and sustainable manner. In building technology-based school branding, digital public relations serve as a communication specialist and content creator, a facilitator of public interaction, a reputation manager and cyber crisis manager, as well as a data analyst to evaluate the effectiveness of digital communication strategies. Optimizing these roles can strengthen the school’s identity, increase the institution’s visibility, build a positive image, and enhance the school’s competitiveness in the digital age. Thus, the planned and sustainable implementation of digital public relations is a key strategy for strengthening technology-based school branding and supporting effective communication